1983
DOI: 10.1210/endo-112-5-1860
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anti-Relaxin Antiserum on Sperm Motility in Vitro

Abstract: Rabbit anti-relaxin antisera, but not normal rabbit sera, causes a rapid decline of motility of washed human sperm. Preincubation of the antisera with relaxin eliminates this effect. This sperm immobilization effect can serve as a basis of a rapid screening test for anti-relaxin antisera and as a novel adjuvant to barrier contraceptive methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…Data about the role of relaxin in mature spermatozoa are controversial. Whereas some data in the literature support a role for relaxin in sperm motility (Sarosi et al 1983, Essig et al 1982, we detected only low levels of Rxfp1 mRNA in mature spermatozoa, and RXFP1 protein was undetectable (Filonzi et al 2007). Other studies have also failed to find an effect of relaxin on sperm function (Jockenhovel et al 1990, Newinger et al 1990).…”
Section: Relaxin Receptors: Expression and Function In The Male Reprocontrasting
confidence: 62%
“…Data about the role of relaxin in mature spermatozoa are controversial. Whereas some data in the literature support a role for relaxin in sperm motility (Sarosi et al 1983, Essig et al 1982, we detected only low levels of Rxfp1 mRNA in mature spermatozoa, and RXFP1 protein was undetectable (Filonzi et al 2007). Other studies have also failed to find an effect of relaxin on sperm function (Jockenhovel et al 1990, Newinger et al 1990).…”
Section: Relaxin Receptors: Expression and Function In The Male Reprocontrasting
confidence: 62%
“…The present study provides no evidence that relaxin binds to germ cells within the testis. This finding is inconsistent with limited evidence that endogenous relaxin within the seminal plasma of humans and pigs contributes to normal motility of the spermatozoa [32][33][34]. In view of the limited number of studies and the inconsistencies among existing findings, it remains to be established that relaxin has a physiologic role(s) in the male in any species.…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, the presence of Rxfp1 receptor on spermatozoa would help explain many studies that suggest that relaxin stimulates sperm motility. For example, antiserum against relaxin reduces sperm motility [47], relaxin stimulates sperm motility and attenuates the decline in the percentage of motile spermatozoa [48], helps restore decreased sperm motility [48], and improves penetration of spermatozoa into cervical mucus [50]. Finally, Carrell et al [50] demonstrated that recombinant relaxin binds to sperm with high affinity.…”
Section: Discussionmentioning
confidence: 99%